PRAKTIK KETERAMPILAN MENTORING PENGUJI PPG DENGAN ONLINE ROLE PLAYING - Fhela Vhantoria Ningrum; Rulik Setiani (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2025)
The understanding of mentoring skills among lecturers and teachers is very low if it is only conveyed in the form of material in a training session without any real-world application. The quality of lecturers and teachers in mentoring affects the success of PPG students in obtaining teaching certificates. The purpose of this community service is to improve the mentoring skills of lecturers and teachers through online role playing. Role-playing presents realistic scenarios according to each participant's role. Therefore, this community service is expected to enable lecturers and mentor teachers to become quality mentors, which is one of the determinants of the quality of PPG student graduates. The implementation of the community service activity consists of preparation, implementation, and evaluation. This community service was carried out on September 9-11, 2025, with 39 participants. Participants were randomly divided into 8 groups. The main result of this PKM activity was 8 videos of role-playing mentoring skills for PPG. The benefit of this activity is that role-playing is intended to make lecturers and mentor teachers consciously feel that they are in various positions. The positions referred to are Field Supervisor Lecturer, Mentor Teacher, Peer, or PPG student being tested. Additionally, lecturers and examiners can understand the 9 roles of a mentor and the stages of mentoring. This community service has a positive impact on improving the mentoring skills of lecturers and teachers in guiding PPG students. The evaluation of this community service is that the lack of time allocation resulted in the PPL mentoring stages not being able to be completed.